Looking Back, Thinking Forward: How a Television Series Facilitated the Development of the Social Work Profession in Hong Kong. (2nd September 2020) - Kwan, Chi Kin; Cheung, Oi Ngor
Abstract: The healthy development of the social work profession rests on the public's understanding and trust. The media play a significant role in shaping the public image of social work. This article describes a focus group study that was designed to retrace the long-term impact of an iconic television series in 1976 on the public's reception of the nascent profession of social work amongst a group of social work practitioners. Four focus groups were conducted with thirty practicing and retired social workers. The content of the focus group discussions was coded and analysed to generate three major themes: (i) the television series gave a real-world articulation of the work of social workers and catalysed the profession's public receptivity; (ii) it inspired a call amongst conscientious young people to join the profession; and (iii) it contributed to the construction of social workers' professional identity. The findings demonstrate the contribution of this television series, hence the role of media, to the early development of professional social work in Hong Kong.